2000
DOI: 10.1046/j.1365-2958.2000.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacteriophage T4 anti‐sigma factor AsiA is not necessary for the inhibition of early promoters in vivo

Abstract: Bacteriophage T4 early promoters are utilized immediately after infection and are abruptly turned off 2–3 min later (at 30°C) when the middle promoters are activated. The viral early protein AsiA has been suspected to bring about this transcriptional switch: not only does it activate transcription at middle promoters in vivo and in vitro but it also shows potent anti‐σ70 activity in vitro, suggesting that it is responsible for the shut‐off of early transcription. We show here that after infection with a phage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…When AsiA was described as the ¢rst anti-sigma factor, it was shown that AsiA inactivates the c 70 in vitro to inhibit the transcription of early promoters that carries the conserved 310 and 335 elements. However, recent in vivo work demonstrated that deletion of asiA had no e¡ect on the inhibition of the early promoters [21]. Another line of evidences has suggested that AsiA acts as a switching molecule that alters the promoter preference of c 70 .…”
Section: Discussionmentioning
confidence: 99%
“…When AsiA was described as the ¢rst anti-sigma factor, it was shown that AsiA inactivates the c 70 in vitro to inhibit the transcription of early promoters that carries the conserved 310 and 335 elements. However, recent in vivo work demonstrated that deletion of asiA had no e¡ect on the inhibition of the early promoters [21]. Another line of evidences has suggested that AsiA acts as a switching molecule that alters the promoter preference of c 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The AsiA- 70 interaction is regarded as the pivotal event in the transition between T4 early and middle transcription: in vitro it both inhibits the recognition of most host promoters and early T4 promoters and stimulates T4 middle-mode transcription (180,425,848,849,1104). However, in vivo, defective asiA mutants do not prolong early transcription (858), suggesting that other proteins (i.e., ModA and ModB) turn off most early T4 promoters. MotA is a DNAbinding transcriptional activator protein that binds to the MotA box sequence (Fig.…”
Section: Middle Transcriptionmentioning
confidence: 99%
“…Assigning this function is a long-standing and unresolved question in phage T4 biology (10). It has been recently shown, however, that this transcription shutoff also occurs in the absence of AsiA (11), although the same study confirmed that transcription of E. coli genes is rapidly and strongly inhibited in vivo when AsiA is overproduced.…”
mentioning
confidence: 92%